The Indonesian Right To Development: From A Perspective Of Maritime Transport Services (MTS) Sector Under WTOGATS - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
Human rights, globalization and development are three big issues entering the XXI century. Globalization is argued to be positive in development. Consequently, it promotes human rights. On the other hand, globalization is also argued that it threatens human rights when globalization dominates the development process especially for the developing countries. This essay highlights those relations whether globalization marked by the WTO/GATS threatens or supports the Indonesia's right to development for implementing the Maritime Transport Services (MTS) under the auspices of the GATS' rules. It reveals that the globalization is a fact rather than a fiction. As a fact, it needs many supra structural and infra structural adjustments on the MTS in Indonesia. So, reform on MTS is a must to cope with.